Recent advances in the managements of type 2 diabetes mellitus and natural hypoglycemic substances - Chong Ning; Yuhan Jiao; Jiaqi Wang; Weiwei Li; Jingqiu Zhou; Yi-Chieh Lee; Dik-Lung Ma; Chung-Hang Leung; Rugang Zhu; Hui-Min David Wang (Food Science and Human Wellness)
ABSTRACT: Diabetes has become a global concern at present, among which type 2 diabetes mellitus (T2DM) accounts for approximately 90 %–95 % of patients. T2DM is a type of metabolic disorder syndrome that results from a genetic defect, and it is based on insulin resistance and an insulin secretion disorder. The occurrence of T2DM is usually the outcome of both genetic and environmental factors and their interactions. The etiology and pathogenesis of diabetes have not been fully elucidated, and no radical therapeutic cure has been found. Patients with T2DM suffer from complications such as the development of a chronic hyperglycemic condition and even serious metabolic disorders and organ damage in the body and depression and dementia, in addition to other chronic complications. Many studies have suggested that diet is crucial in the development of diabetes and the control of blood glucose. Natural substances have the characteristics of low toxicity and few side effects and may be key to the development of diabetic health products and preventive treatments. This paper reviews the etiology, pathogenesis, risks, treatments and diets related to T2DM to summarize the types of recently available natural products, from both local and foreign sources, for lowering blood glucose at home and their application in supplementary hypoglycemic foods. The key findings and conclusions suggest that there are various known T2DM-inducing factors, including genetic and environmental factors and three types of hybrid factors.